The Failure of MINUSCA as Peacekeeping Force in the Central African Republic (CAR) in 2013-2015 - SD, Hardi Alunaza; Sherin, Virginia (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2018)
Since Bozizé led the CAR from March 15, 2003, to March 24, 2013, there has been resistance from some of the rebel forces. The rebellion continues because of the economic and political weaknesses in the CAR government. One of them comes from an opposition coalition known as Séléka who staged a rebellion in 2013 with the aim of overthrowing the Bozizé regime. After the fall of Bozizé, CAR's condition has worsened because Séléka rebels have committed gross human rights violations in the CAR. This is where the conflict develops from the conflict that was originally just a conflict of government-opposition, then widened and turned to religious conflicts. As a result, questions arise about the efforts and involvement of third parties in conflict resolution within the CAR and the social impacts of the conflict. This article attempts to answer questions which focuses on the involvement of third parties as peacekeepers in conflict areas. In this case, the authors use qualitative research methods in the form of literature studies such as books, journals, and scientific articles in supporting the final explanation. The result of this paper shows that the failure of Multidimensional Integrated Stabilization Mission in the Central African Republic (MINUSCA) as a peacekeeping force in the conflict in CAR in 2013-2015 is caused by human rights violation in the form of sexual exploitation. This has had a social impact on the lives of communities, especially women and children, suffer from physical and mental trauma resulting from conflict and become victims of human rights violations committed by MINUSCA.